Electromyographic evaluation of mastication and swallowing in elderly individuals with mandibular fixed implant-supported prostheses - Giédre Berretin-Felix; Hugo Nary Filho; Carlos Roberto Padovani; Alceu Sergio Trindade Junior; Wellington Monteiro Machado (University of São Paulo, 2008)
This study evaluated the effect of implant-supported oral rehabilitation in the mandible on the electromyographic activity during mastication and swallowing in edentulous elderly individuals. Fifteen patients aged more than 60 years were evaluated, being 10 females and 5 males. All patients were edentulous, wore removable complete dentures on both dental arches, and had the mandibular dentures replaced by implant-supported prostheses. All patients were submitted to electromyographic evaluation of the masseter, superior orbicularis oris muscles, and the submental muscles, before surgery and 3, 6 and 18 months postoperatively, using foods of different textures. The results obtained at the different periods were analyzed statistically by Kruskal-Wallis non-parametric test. Statistical analysis showed that only the masseter muscle had a significant loss in electromyographic activity (p<0.001), with a tendency of similar response for the submental muscles. Moreover, there was an increase in the activity of the orbicularis oris muscle during rubber chewing after treatment, yet without statistically significant difference. Mandibular fixed implant-supported prostheses in elderly individuals revealed a decrease in electromyographic amplitude for the masseter muscles during swallowing, which may indicate adaptation to new conditions of stability provided by fixation of the complete denture in the mandibular arch.